Mixed Weyl semimetals and low-dissipation magnetization control in insulators by spin–orbit torques. Issue 1 (December 2017) - Hanke, Jan-Philipp; Freimuth, Frank; Niu, Chengwang; Blügel, Stefan; Mokrousov, Yuriy
Abstract Reliable and energy-efficient magnetization switching by electrically induced spin–orbit torques is of crucial technological relevance for spintronic devices implementing memory and logic functionality. Here we predict that the strength of spin–orbit torques and the Dzyaloshinskii-Moriya interaction in topologically nontrivial magnetic insulators can exceed by far that of conventional metals. In analogy to the quantum anomalous Hall effect, we explain this extraordinary response in the absence of longitudinal currents as hallmark of monopoles in the electronic structure of systems that are interpreted most naturally within the framework of mixed Weyl semimetals. We thereby launch the effect of spin–orbit torque into the field of topology and reveal its crucial role in mediating the topological phase transitions arising from the complex interplay between magnetization direction and momentum-space topology. The presented concepts may be exploited to understand and utilize magnetoelectric coupling phenomena in insulating ferromagnets and antiferromagnets. Electric-field control of magnetization switching is highly promising for low-dissipation spintronics. Here, the authors propose an electrically induced topological phase transition mediated by spin orbit torques as attractive way to control magnetization in absence of longitudinal charge currents.